Increasing community income with processing of plastic waste in Helvetia village - Lumbanraja, Prihatin; Lubis, Arlina Nurbaity; Hasibuan, Bebby Kandida (Talenta Publisher, 2019)
The presence of waste in the environment is the root of many contradictions. Garbage can cause a variety of diseases, moving comfort, mosquito nests, and apart damaged view around. The presence of garbage makes the environment not beautiful. Nevertheless, many people have contributed to make waste increasingly pollute the environment. Scavengers are one of the professions that help plastic waste with low economic potential. While behind the negative side of waste, this can still be optimized by management so as to provide good economic value. Processing waste also encourages the level of monitoring of waste in the environment which makes it more beautiful. The dedication activities that have been carried out raise several issues at once. First is the empowerment of community groups who are scavengers without active groups. Second is increasing public awareness to dispose of garbage in landfills and classifying waste disposal so that it can be better and easier to manage others. Third is pollution caused by unmanaged waste, especially non-organic waste such as plastic. Community service activities help increase the economic and financial activities of partners and groups by helping to start a business as an expertise development that is usually done as a scavenger. Science and technology transfers consisting of management, business management, production management, finance, and groups will be given to partners. In addition, this service is a partner of change that helps change the community so that they are aware of waste disposal. This change will also benefit partners who will more easily obtain raw materials for their production.